Multi-Dimensional Gene Regulation in Innate and Adaptive Lymphocytes: A View From Regulomes - Fernando, Nilisha; Sciumè, Giuseppe; O’Shea, John J.; Shih, Han-Yu (Frontiers in Immunology, 2021)
The precise control of cytokine production by innate lymphoid cells (ILCs) and their T cell adaptive system counterparts is critical to mounting a proper host defense immune response without inducing collateral damage and autoimmunity. Unlike T cells that differentiate into functionally divergent subsets upon antigen recognition, ILCs are developmentally programmed to rapidly respond to environmental signals in a polarized manner, without the need of T cell receptor (TCR) signaling. The specification of cytokine production relies on dynamic regulation of cis-regulatory elements that involve multi-dimensional epigenetic mechanisms, including DNA methylation, transcription factor binding, histone modification and DNA-DNA interactions that form chromatin loops. How these different layers of gene regulation coordinate with each other to fine tune cytokine production, and whether ILCs and their T cell analogs utilize the same regulatory strategy, remains largely unknown. Herein, we review the molecular mechanisms that underlie cell identity and functionality of helper T and ILCs, focusing on networks of transcription factors and cis-regulatory elements. We discuss how higher-order chromatin architecture orchestrates these components to construct lineage- and state-specific regulomes that support ordered immunoregulation.